2003
DOI: 10.1002/cncr.11081
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node versus axillary lymph node dissection for early‐stage breast carcinoma

Abstract: The selectivity of reactions on active patches over those on a partially active carrier surface is investigated for patch‐covered spheres. The effects of relevant parameters including patch and carrier reactivities, patch coverage, patch size, and patch separation state are studied. The selectivity is found to increase with increasing relative dominance of the patch reactivity over the carrier reactivity and patch coverage, as expected. Interestingly, it also increases with decreasing patch size and increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 52 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…[16][17][18][19][20][21] The accuracy of histopathologic evaluation of SLNs for melanoma is significantly improved with the use of immunohistochemical stains. [4][5][6][7] Routine H&E staining alone has been shown to yield a false-negative rate of 10-34%.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] The accuracy of histopathologic evaluation of SLNs for melanoma is significantly improved with the use of immunohistochemical stains. [4][5][6][7] Routine H&E staining alone has been shown to yield a false-negative rate of 10-34%.…”
Section: Discussionmentioning
confidence: 99%
“…Aspects of breast cancer treatment have been previously associated with upper arm morbidity, including surgical manipulation of the axilla with either sentinel lymph node biopsy or axillary node dissection 8,10,29,30 and radiation therapy 6,9,13,15,31 . The advent of less invasive sentinel lymph node evaluation will reduce the prevalence of axillary node dissection among breast cancer patients below that observed in this population, although patients with a positive sentinel node will often still receive an axillary node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…10,[14][15][16] Studies of quality of life in patients treated for breast cancer have shown prolonged decreases in quality of life for those with lymphedema and other chronic arm symptoms resulting from axillary dissection. [7][8][9]17 At present, there are no effective therapies to reverse established lymphedema. 2 As lymphedema after axillary dissection cannot be 'cured', or even reliably prevented, identification of alternatives to standard axillary dissection have been sought.…”
Section: Sentinel Node Biopsy: Reducing the Morbidity Of Axillary Stamentioning
confidence: 99%